Niveles de ansiedad en pacientes de 6 a 14 años que han sufrido fracturas y serán intervenidos quirúrgicamente en el Área de Pediatría Traumatológica, de los hospitales de la ciudad de Loja, en el período mayo-octubre del 2014 - Jiménez Sarango, Fanny Maribel (2014)
Child anxiety takes shape as an experience negative which usually happens before a situation threatening both real and imagined where arise the same aforementioned physiological responses such as sweating, palpitations, etc. The Anxiety as excitement is constituent part of human development can be experienced as emotional discomfort associated with the anticipation of danger or threat. Anxiety levels were identified through the Test of anxiety which I think and feel (CMAS-R) in patients who have suffered fractures and will be operated; which, a population sample of 52 patients aged 6 14 years, hospitalized in the areas of Pediatric trauma at the Hospital Manuel Ygnacio Monteros (IESS) and Hospital Regional Isidro Ayora from the city of Loja, it applied the test of manifest anxiety "what I think and feel (CMAS-R)" which allowed to measure three areas such as: Physiological anxiety - anxiety hypersensitivity and social concerns concentration. Demonstrate that in the area of physiological anxiety prevails with 49 male gender in relation to the feminine presenting a 27, in the area of concern hypersensitivity prevails equally masculine gender with a 27 unlike the female gender with a 20, and in the third area concerns social concentration prevails the female gender with a 53 in contrast to the masculine gender with a 24. Developed a psychotherapeutic intervention Plan directed to patients and their families the same whose purpose was to prevent psychological disorders and lower anxiety levels by stressful events that lead to surgery. The information gathered through this study will help the design of psychotherapeutic interventions appropriate for patients who are hospitalized and will undergo surgery as response to this problem is proposed a treatment plan in children aged 6 to 14 in hospitals in the city of Loja, in order to reduce anxiety levels through techniques; Play therapy, cognitive restructuring and the detection of Distorsionados thoughts; Implement as policy hospital surgical psychoprophylaxis as a therapeutic method in favour of the reduction in the levels of anxiety in patients with fractures; and, that this proposal for psychological intervention is put into practice by other hospital areas since the psycho is a key contributing factor to recover effectively and efficiently for the majority of physical pathologies. Keyword:: Fractured patients, anxiety, and psychological proposal.